Changes in milk production and economic analysis in relation with the temperature-humidity index in Korean Holstein cows - Jongil Jeong; Seokhyun Lee; Kwi-ryong Park; Jisu Kim; Mirae Kim; Hyeonho Lee; Minji Seo; Jiyeon Han; Gyeonglim Ryu; Daehyun Kim (Journal of Animal Reproduction and Biotechnology, 2025)
Background: Dairy cows exposed to heat stress have reduced milk production, milk quality, and conception rates, leading to lower profits. This study was conducted to analyze the effect of heat stress according to Temperature-Humidity Index (THI) on the milk production of Korean Holstein cows. Methods: Monthly maximum temperature and average relative humidity data from January 2017 to August 2024 were obtained from 62 observation points used by the Korea Meteorological Administration to calculate the national average. Using this data, the THI, a key indicator for assessing heat stress in Korean Holstein cows, was calculated. Additionally, data from 240,088 Korean Holstein cows, collected through tests conducted by the Dairy Cattle Improvement Center of the NH-Agri Business Group, were analyzed. Results: Comparative analysis of the relationship between THI and milk production revealed that milk yield remained relatively stable until THI reached the “very severe” heat stress threshold (THI ≥ 79). Beyond this level, milk production showed a tendency to decline. Conversely, when THI dropped below this threshold, milk yield tended to recover. Notably, the temperature in September, typically considered part of the autumn season, has been rising in recent years, with THI values now approaching the very severe stress level (THI ≥ 79). Conclusions: These findings suggest that establishing an appropriate farm environment and implementing systematic THI management are essential for mitigating the decline in milk production, as well as the associated economic losses, caused by rising domestic temperatures due to global warming.